Learner Autonomy: Concept and Considerations (Journal of NELTA, 2011)
"Give me a fish and I eat for a day. Teach me to fish and I eat for a lifetime." This proverb taken from Chinese culture is associated with learner autonomy. Once learning used to be the matter of receiving the body of knowledge which could then be used for the rest of life. But such view has been nonsense in this fast-paced world. Therefore, the learners should be provided with the skills necessary for the lifelong pursuit for knowledge. This article begins with the general concept of autonomy and goes on to consider different aspects of autonomy. It insists that learner autonomy does work in any culture provided that the teacher also has autonomy to some extent and curriculum is designed accordingly. While it highlights that total autonomy is neither feasible nor desirable in formal language learning contexts, it argues that learner autonomy is necessary for making someone lifelong learner.Key words: Learner autonomy; Teacher autonomy; Curriculum; Culture; ActivitiesJournal of NELTAVol. 15 No. 1-2 December 2010Page: 114-120Uploaded date: 4 May, 2011DOI: 10.3126/nelta.v15i1-2.4617